Effect of vacuum impregnated fish gelatin and grape seed extract on moisture state, microbiota composition, and quality of chilled seabass fillets - Zhao, Xue; Chen, Lin; Wongmaneepratip, Wanwisa; He, Yun; Zhao, Lin; Yang, Hongshun (Food chemistry, 2021)
•Fish gelatin-grape seed extract (FGG) showed synergistic preservative effect.•FGG retarded the water migration in seabass fillets during chilled storage.•FGG inhibited the growth of Pseudomonas, Aeromonas, and Shewanella.•Microbiota composition in chilled seabass was greatly changed by FGG.•FGG postponed discoloration and inhibited accumulation of biogenic amines. The effect of fish gelatin (FG) and grape seed extract (GSE) on microbiota composition and moisture state of fish was unexplored. Herein, this study aimed to evaluate the single and combined (FGG) effects on seabass during storage (4 °C) with assistant of vacuum impregnation and to elucidate the underlying preservative mechanism. As suggested by low-field NMR and magnetic resonance imaging, FGG-treated seabass presented higher water holding capacity by controlling transformation from immobilised to free water. Moreover, the total viable count and spoilage bacteria were reduced by > 1 log CFU/g as compared to the control. Changes in microbial flora analysed using high throughput sequencing further indicated that GSE contributed to the notably suppressed growth of Pseudomonas. Also, the accumulation of biogenic amines especially putrescine was decreased (over 0.5-fold) under the combination treatment as compared to the control (P < 0.05). The results suggest that FGG is promising for seabass preservation.